Digital Frames and Visible Grain: Spatial and Material Reintegration in Irréversible. - De Los Rios, Riccardo; Davis, Robert (Film Criticism)
The article examines the spatial and material reintegration in the thriller film "Irréversible," by Gasper Noé. The authors argue that the thriller film employs digital technologies in order to deconstruct, as well as digital visual effects in order to overthrow the expectations of its viewers about time and space. It is believed that this use of digital technologies enables the film to decline to involve in delusions of moral certainty. It is concluded that enhancement technologies were used in the film in order to explore changing identity.